EFEKTIVITAS PEMBELAJARAN DARING MENGGUNAKAN GOOGLE CLASSROOM DAN ZOOM MEETING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XII MIPA SMA NEGERI 6 MERANGIN - Mardiani, S.Pd (Pendidikan Matematika | STKIP YM Bangko, 2021)
This study aims to describe the effectiveness of online learning using google classroom and zoom meeting on the physics learning outcomes of class XII MIPA students at SMA Negeri 6 Merangin. This research is an experimental study with a randomized subject posttest only control group design. Sampling using simple random sampling technique, selected as experimental class 1 is class XII MIPA 1 and experimental class 2 is class XII MIPA 2. The data collection technique uses tests with instruments in the form of items to measure physics learning outcomes. The normality test used the Kolmogorv-Smirnov formula, the homogeneity test used the Levenne test, and the hypothesis test used the independent sample t-test formula. From the data analysis, it is known that the value of tcount = 7.183 and ttable = 1.668, it turns out that tcount > ttable, this means that H0 is rejected and H1 is accepted. Based on this, it can be concluded that the results of learning physics using online learning using google classroom and zoom meetings are better than using only google classroom for students of class XII MIPA SMA Negeri 6 Merangin.